The Emergence and Spread of the Buddhist Tārā Cult in India between 7th Century CE and 11th Century CE with Special Reference to the Sirpur Tārā Bronzes. (22nd June 2021) - Singh, Saurabh
Sirpur (Lat. 21° 25'N, Long. 82° 11'E) is a small village on the right bank of Mahanadi in the Mahasamund District of Chhattisgarh. It is an important archaeological site and archaeological excavations at Sirpur revealed that it was an important centre of Mahayana Buddhism in Central India. Numerous bronze images of the Buddha and Buddhist deities such as Bodhisattva Avalokiteśvara, Tara etc. were found from Sirpur. In this paper, an attempt has been given to discuss the sculptural and iconographic bronze images of Tara from Sirpur. A comparative study of these Tara images with the Tara bronze images found in other Buddhist sites of India has been carried out. The article will highlight the iconographic features of the Buddhist goddess Tārā and her importance in the contemporary religious settings during the 5 th –6 th centuries CE.